2020
DOI: 10.1109/jsen.2020.2982568
|View full text |Cite
|
Sign up to set email alerts
|

Validating Commercial Wearable Sensors for Running Gait Parameters Estimation

Abstract: A growing number of people all over the world are running. Gathering in-field data with wearable sensors is attractive for runners, clinicians and coaches to improve running performance, avoid injury or return to running after an injury. However, it is yet to be proven that commercially available wearable sensors provide valid data. The objective of this study was to assess the validity of five wearable sensors (Moov Now TM , MilestonePod, RunScribe TM , TgForce and Zoi) to measure ground reaction force relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
1
29
1
Order By: Relevance
“…The relationship between AVLR and PPA from the shoemounted IMUs (IMeasureU-Shoe: r = 0.49 overall; RunScribe Impact: r = 0.55 overall; RunScribe Shock: r = 0.47 overall) was not only significant, but higher than in previous studies that fixed the IMU to the heel instead of the laces (Cheung et al, 2019;Pairot de Fontenay et al, 2020). This suggests that the lace-mount might be a better location to act as a proxy for GRF loading rates when compared with the heel.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The relationship between AVLR and PPA from the shoemounted IMUs (IMeasureU-Shoe: r = 0.49 overall; RunScribe Impact: r = 0.55 overall; RunScribe Shock: r = 0.47 overall) was not only significant, but higher than in previous studies that fixed the IMU to the heel instead of the laces (Cheung et al, 2019;Pairot de Fontenay et al, 2020). This suggests that the lace-mount might be a better location to act as a proxy for GRF loading rates when compared with the heel.…”
Section: Discussioncontrasting
confidence: 54%
“…Distally-placed accelerometers may also more closely represent the accelerations experienced by the foot/ankle (Sheerin et al, 2019 ). However, positive associations between impact loading (average vertical loading rate; AVLR) and PPA of shoe-mounted IMUs have been poor, especially when attached to the heel of the shoe (Cheung et al, 2019 ; Pairot de Fontenay et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accelerometer Tgforce (v2.0.0.10) will be taped to the anteromedial aspect of the subject's distal tibia [20]. The study of Pairot de Fontenay and colleagues [41] assessed the…”
Section: Rehabilitation Programs (Independent Variables)mentioning
confidence: 99%
“…Morbidoni et al [33] utilise electromyography signals for deep learning classification of stance, swing phases during natural walking. Pairot et al [34] determined the validity of commercially available, wearable sensors by monitoring gait during running and concluded that only few metrics measured by commercially available sensors are valid. Park et al [35] developed a real-time healthcare monitoring system for monitoring gait and vital signs, and utilised machine learning classification for health conditions, such as disordered gait and onset of stroke.…”
Section: Related Workmentioning
confidence: 99%